A review of apixaban for stroke prevention in atrial fibrillation: insights from ARISTOTLE. (2013) - Hess, Connie N; Al-Khatib, Sana M; Granger, Christopher B; Lopes, Renato
Atrial fibrillation (AF) is associated with significant mortality and morbidity, and stroke represents the most-feared complication. Consequently, AF treatment has focused on thromboprophylaxis, with warfarin as the mainstay of therapy. However, concerns over ease of use and safety have limited its use. Three novel oral anticoagulants have been approved for use in stroke prevention in AF based on randomized data: 1) dabigatran, studied in Randomized Evaluation of Long-term Anticoagulation Therapy (RE-LY); 2) rivaroxaban, studied in Rivaroxaban Once-daily, Oral, Direct Factor Xa Inhibition Compared with Vitamin K Antagonism for Prevention of Stroke and Embolism Trial in Atrial Fibrillation (ROCKET AF); and 3) apixaban, studied inApixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation (ARISTOTLE). In this review, we focus on apixaban and discuss subgroup analyses that have been performed in the three trials comparing novel oral anticoagulants with warfarin. We conclude with recommendations regarding further investigations.